Endothelial Cell Distribution After Flow Exposure With Two Stent Struts Placed in Different Angles - Wang, Zi; Putra, Narendra Kurnia; Anzai, Hitomi; Ohta, Makoto (Frontiers in Physiology, 2022)
Stent implantation has been a primary treatment for stenosis and other intravascular diseases. Such metal mesh structures are usually deployed at the target positions on the blood vessels. However, the stent expansion procedure might cause endothelium lesion. Moreover, the structure of the stent on the wall could disturb the blood flow environment near the wall of the blood vessel. These changes could damage the vascular innermost endothelial cell (EC) layer and pose risks of restenosis and post-deployment thrombosis. However, the arterial flow is complex due to the arterial shape. This research aims to investigate the effect of flow alterations on EC distribution in the presence of stent struts within the parallel flow chamber to control the flow around the stent struts. To study how the stent strut presence impacts EC migration and the endothelialization effect on the surface of the struts, two stent struts were placed with specific orientations and positions on the EC layer in the flow chamber. After a 24-hours exposure under wall shear stress (WSS), we observed the EC distribution conditions. We also conducted computational fluid dynamics (CFD) simulations to calculate the WSS distribution. High EC-concentration areas on the bottom plate corresponded to the high WSS by the presence of the two stent struts. The endothelialization rate, represented by EC density, on the downstream sides of both stent struts was higher than that on the upstream sides. These observations were made in the flow recirculation at the gap area between two stent struts. On two side surfaces between the gaps, meaning the downstream at the first and the upstream at the second struts, EC density differences on the downstream surfaces of the first stent strut were higher than on the upstream surfaces of the second stent strut. Finally, EC distribution varied along the struts when the struts were placed at tilted angles. To find the relation between the WSS and EC distributions on the fluorescence images, CFD simulation-based WSS prediction could be helpful for the EC distribution.